PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA POLA SWADAYA DI DESA IGAL KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Denny Kristian; Eri Sayamar; Cepriadi Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study are: (1).To determine the implementation of agricultural extension in the village of Igal; (2).To determine the role of education and the empowerment of farmers in the coconut farm self pattern; (3) To analyze the relationship counseling role towards the empowerment of farmers. This research was conducted in the village of Igal District of Mandah Indragiri Hilr. The sampling method used is purposive sampling method with consideration that the location of its extension activities and the active oil production areas. 30 self-help coconut farmers were taken as respondents. Analyzing the validity and reliability of measuring instruments. Analysis of the data to answer the first goal is to use descriptive qualitative, the second destination using a Likert scale. On the third goal using Spearman rank correlation analysis. The results showed: (1).In the implementation of the extension such as the elements of counseling in the village of Igal quite done well. (2). The average role of counseling in the Village Igal Subdistrict Mandah Indragiri Hilir Regency already "Role". Where the activities "Role" there are 11 indicators of 21 existing indicators. While the"Quite Simply" there are 10 indicators of 21 existing indicators. The rest of the activities do not get the category"Very Less Action"or"Less Action". This shows that the extension activities in Igal Village,Mandah Sub District have been good for the coconut farmers in Igal village (3). Relationship counseling role towards the empowermentof self-help coconut farmers patterns are at the level of the relationship is strong enough,powerful and significantKeywords: Role of extension, Empowerment, Coconut Farmers Self Pattern